Factores de riesgo asociados a la prevalencia de enfermedad periodontal en estudiantes de odontología de II-III semestre de la universidad Antonio Nariño sede Cúcuta (2024)
Periodontal disease is a chronic infectious and inflammatory process that affects the supporting and supporting tissues of the tooth, whose main etiology is dental biofilm. The sample was made up of 60 students from the II-III semester of dentistry who signed the informed consent and participated voluntarily. A medical history was completed for each student, including a complete periodontal examination. The Oleary index was used to measure the level of oral hygiene, dental prophylaxis and a stress test were performed and a survey was applied to measure the level of knowledge acquired. The periodontal diagnoses issued were based on the 2017 classification of periodontal and peri-implant conditions and diseases.